P083 Undergraduate rheumatology teaching in the UK: a survey of teachers. (23rd April 2022) - Watson, Pippa; Coady, David; Southam, Daisy; Andrew, Donna; Logan, Victoria; Wakefield, Richard
Abstract: Background/Aims: Since the last UK wide survey of undergraduate (UG) education in rheumatology in 2000 (1), the landscape of both university teaching and clinical services has altered significantly. There has been an increase in the number of medical schools (26 to 37), rise in student numbers, curricula expansions, plus the impact of Covid-19. This survey evaluates the current status of rheumatology teaching in the UK and highlights areas for the Rheumatology community to consider when planning future training. Methods: In early 2021, a 'Survey Monkey' was emailed to named MSK leads representing all 37 UK schools. This included open and closed questions and explored themes from previous published surveys. Reminders were sent after 2 and 4 weeks. Results: Responses were received from 34/37 (92%) schools. There is wide variation in what, when and how teaching is delivered, but the vast majority deliver rheumatology specific teaching spread across years 1-5. Overall length of clinical rheumatology exposure varied from 3 days to 7 weeks, delivered either as separate days (e.g. in integrated placements or PBL), as formal blocks (often with orthopaedics) or within a student selected component. Approximately 25% of teaching is delivered in primary care. Most is delivered in Year 4. Most schools have a designated rheumatology lead: a clinical academic or clinician. Teaching is acknowledged in most job plans with educational roles discussed at appraisals. Small group teaching remains the most common method of delivering formal teaching, followed by on-line learning and lectures. The majority of teaching is delivered by consultants, trainees and research fellows. A wide range of barriers were noted including competing pressures from clinical work, lack of physical space for teaching and the volume of medical students. Due to COVID-19, 50% of medical schools suspended placements at some point during the pandemic. 70% of schools reported a 50-75% reduction in patient contact time for students reflecting the national data re: 20% of rheumatology departments functioning at less than 50% during the pandemic (2). Many schools reported designing new innovative (often online) resources to support learning during the pandemic. Available resources such as the Versus Arthritis patient examination videos (available on YouTube) and flipbook were noted to be particularly useful learning resources. Conclusion: Over the past 20 years, rheumatology UG teaching has remained strong but time for dedicated rheumatology training has reduced in some centres. Remote learning has become more common, which coupled with Covid, has raised concerns amongst teachers that students are not getting sufficient clinical exposure. There is interest for a rheumatology UG community to create and share online resources and act as a source of support. Disclosure: P. Watson: Other; Pip is employed by the BSR as eLearning editor. D. Coady: None. D. Southam: Other; Daisy is employed by the BSR as head of Education. D. Andrew: None. V. Logan: Other; Victoria is employed by the BSR as Director of Marketing and Education. R. Wakefield: None.